Countertopographies of Agriculture Gender, Food Production, and Development in a Globalizing World - Mullaney, Emma Gaalaas (Consilience, 2012)
This paper is being published in Consilience through a collaboration with SustainUS. This paper examines the potential of geographic analysis to empower rural women through development policy. Women have remained at the margins of agricultural policy in spite of decades of research documenting their importance in maintaining food security and crop diversity, and continued national and international efforts at gender mainstreaming. Existing approaches to gender analysis are inadequate in dealing with global social and institutional structures that gender mainstreaming seeks to transform. A ‘contertopgraphic’ methodology, developed by geographers to trace structural similarities between different places is used to analyze the dynamic connections between gender, food production, and development. Through the juxtaposition of rural women’s experiences in four distinct agricultural settings, this paper demonstrates how inequality and inequity in different locales are the result of broad-scale political and economic change. A geographic framework may be more suitable to recognize and address the disempowerment of rural women in a globalizing world.